2021
DOI: 10.1016/j.aca.2021.338466
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic flow modulation for improved electrokinetic preconcentration: Application to capillary electrophoresis of fluorescent magnetic nanoparticles

Abstract: It is reported in this study a new approach for modulation and even suppression of the electroosmotic flow (EOF) to achieve better electrokinetic preconcentration in capillary electrophoresis This is based on the augmentation of the buffer's concentrations to very high levels (more than a thousand of mM) without recourse to any dynamic/permanent coating nor viscous gel. The use of large weakly charged molecules as background electrolyte's constituents allows working at extreme concentration ranges without pena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Nguyen et al. demonstrated the EOF‐assisted electrokinetic preconcentration using CE‐LIF to provide a better electrokinetic preconcentration of core‐shell magnetic nanoparticles (CSMNPs) having high potential for diagnostics and controllable cargos for nanomedicine [124]. The principle was based on the augmentation of the buffer's concentrations to very high levels without any dynamic or permanent coating or viscous gel.…”
Section: Selected Applications In the Pharmaceutical And Related Bioc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al. demonstrated the EOF‐assisted electrokinetic preconcentration using CE‐LIF to provide a better electrokinetic preconcentration of core‐shell magnetic nanoparticles (CSMNPs) having high potential for diagnostics and controllable cargos for nanomedicine [124]. The principle was based on the augmentation of the buffer's concentrations to very high levels without any dynamic or permanent coating or viscous gel.…”
Section: Selected Applications In the Pharmaceutical And Related Bioc...mentioning
confidence: 99%
“…This new approach was used for the sensitive determination of CSMNPs with high potential for healthcare applications such as imaging agents for diagnostics and controllable cargos for nanomedicine. Detection and interaction study of CSMNPs could be realized with 350-fold sensitivity improvement [124]. Online SPE-CE-MS was applied for the analysis of peptide biomarkers by Gascon et al [125].…”
Section: Selected Applications In the Pharmaceutical And Related Bioc...mentioning
confidence: 99%
“…To overcome this drawback, LVSS combines with the polarity switching (PS) technique to remove a vacant sample matrix from the capillary to the inlet vial. By employing the PS-LVSS technique, Chinese medicine component [43], magnetic [44], and 3-hydroxyaspartate [45,46] were successfully concentrated and separated in CE. Nguyen et al reported an effective PS-LVSS method for fluorescent magnetic nanoparticles [44].…”
Section: Application Of Field-amplified Sample Stackingmentioning
confidence: 99%
“…By employing the PS-LVSS technique, Chinese medicine component [43], magnetic [44], and 3-hydroxyaspartate [45,46] were successfully concentrated and separated in CE. Nguyen et al reported an effective PS-LVSS method for fluorescent magnetic nanoparticles [44]. By the optimization of the BGE components for controlling electroosmotic flow (EOF), core-shell magnetic nanoparticles were well enriched with the SEF of 350.…”
Section: Application Of Field-amplified Sample Stackingmentioning
confidence: 99%
“…Under these conditions, positive ions tend to thicken in the diffuse layer of the solution near the capillary wall: it is affected by the electric field while the bulk solution is globally neutral. Diffuse layer, globally positive, moves toward the cathode dragging with it the entire solution and giving rise to the EOF [77][78][79][80][81][82][83][84]. Due to the pulling force of the EOF, all molecules in the solution, positive, neutral, and even negative, will migrate toward the cathode.…”
Section: Capillary Electrophoresismentioning
confidence: 99%